As entidades sem fins lucrativos e as politicas públicas federais: Tipologia e análise de convênios e organizaç\~oes (2003-2011) - Felix Lopez; Leonardo Barone (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This paper presents some features of the partnerships and the non-profit organizations (NPOs) that received funds for public policies from the federal government between 2003 and 2011. The analysis is based on a new typology created to define the types of partnerships and their objectives that were implemented via non-profits as well as the intersection of this typology with data available in Fasfil/IBGE and other databases. The evolution of spending on partnerships is demonstrated, as well as their objectives by Ministry and by non-profit organization. The data also provides a better way to evaluate the place and space NPOs fill within federal public policies during the years considered. Although NPOs and their respective areas of collaboration are quite diverse, we found a strong relationship among the types of organizations and their partnership objectives in each area of public policy and/or federal government agency.
Keywords: H40; H49; 330; non-profit organizations in Brazil; voluntary federal transfers; civil society organizations; Brazilian NGOs